The potential use of glow-in-the-dark safety helmet for enhanced worker safety / Mohamad Zulhafriz Mohd Adi ... [et al.] - Mohd Adi, Mohamad Zulhafriz; Mohd Zin, Ida Nianti; Ibrahim, Azira; Wan Ali, Wan Nordiana (2023)
Nighttime construction work poses significant safety risks due to poor visibility, increasing the likelihood of accidents and injuries for both workers and drivers. This paper addresses the need for enhanced worker safety during night shifts and proposes the development and marketability of glow-in-the-dark safety helmets. The research questions focus on the construction of a prototype using an improvised design, the importance of demonstrating the helmet's performance, and the development of commercial viability. The study aims to produce a safety helmet that glows in the dark, improving comfort, visibility, and productivity for construction site workers. The report highlights the limitations of conventional safety helmets in low-light conditions and the higher risks faced by night-shift workers. By incorporating photoluminescent coatings, glow-in-the-dark safety helmets emit light after exposure to natural or artificial sources, significantly improving worker visibility in poorly illuminated areas. The advantages of these helmets include increased visibility, reduced risk of head injuries, improved safety awareness, and enhanced worker morale. The paper also emphasizes the marketability of glow-in-the-dark safety helmets, particularly in industries such as construction, manufacturing, and utilities, where worker safety is paramount. Compliance with safety regulations and the integration of innovative technologies further contribute to their appeal.